2020
DOI: 10.1080/10253890.2020.1781084
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in stress research: a view from the U.S. National Institute of Mental Health

Abstract: The mission of the National Institute of Mental Health is to transform the understanding and treatment of mental illnesses through basic and clinical research, paving the way for prevention, recovery, and cure. In consultation with a broad range of experts, the NIMH has identified a set of priorities for stress biology research aimed squarely at creating the basic and clinical knowledge bases for reducing and alleviating mental health burden across the lifespan. Here, we discuss these priority areas in stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In conclusion, the current studies describe an important correlation of high physiological levels of estradiol to stress-induced memory impairments. This potentially deleterious role of estradiol is novel and underscores the need for careful and nuanced studies of the role of sex and sex steroids on the effects of distinct stresses in distinct contexts ( Simmons et al, 2020 ). Such studies and an improved understanding of the underlying mechanism are a prerequisite for elucidating the biology underlying sex differences in post-traumatic stress disorder and other stress and memory-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the current studies describe an important correlation of high physiological levels of estradiol to stress-induced memory impairments. This potentially deleterious role of estradiol is novel and underscores the need for careful and nuanced studies of the role of sex and sex steroids on the effects of distinct stresses in distinct contexts ( Simmons et al, 2020 ). Such studies and an improved understanding of the underlying mechanism are a prerequisite for elucidating the biology underlying sex differences in post-traumatic stress disorder and other stress and memory-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The latter, in contrast, have typically been collected at a fixed delay after a more persistent stressful experience in order to create a contrast between two conditions (stressed and unstressed). Importantly the effects of acute and chronic stress are frequently different in terms of transcriptomic changes ( Simmons et al, 2020 ). One large gene expression atlas of different kinds of stress in rodent brain meta-analyzed gene expression data from 18 projects studying the effect of stress on the transcriptome of the brain ( Flati et al, 2020 ).…”
Section: Models Of Stress For Transcriptomic Studiesmentioning
confidence: 99%
“…However, neurobiological research on stress has reached a major obstacle - the very “non-specific” nature of the phenomenon has blocked further study ( Simmons et al, 2020 ). The wide variety of ways to induce stress lead to diverse and often contradictory responses in neural circuits.…”
Section: Models Of Stress For Transcriptomic Studiesmentioning
confidence: 99%
“…It has been shown that the corticostriatal circuit, which includes the nucleus accumbens and ventromedial posterior frontal cortex, does indeed differ in the brains of individuals with tinnitus (Leaver et al, 2011). The corticostriatal circuit is part of the general "appraisal network", determining which sensations are important and ultimately affecting how (or whether) those sensations are experienced (Simmons et al, 2020). Our theory of the pathogenetic mechanism of NIHD is schematically summarized in Figure 6.…”
Section: Mechanisms Of Trmsmentioning
confidence: 99%